Trade facilitation and innovation evidence from South Asia Subregional Economic Cooperation countries. - Shepherd, Ben (Metro Manila, Philippines Asian Development Bank, 2018)
Using data from over 120,000 firms in 125 mostly developing and transition economies, this paper examines how trade times affect innovation behavior. Analysis shows that shorter trade times are associated with the introduction of new products and new management systems. From a policy perspective, results suggest that long-run growth in the South Asia Subregional Economic Cooperation (SASEC) countries can be supported in part by improving trade facilitation, where performance lags substantially behind the global frontier. This paper has shown that trade facilitation performance, as measured by the time taken for goods to clear customs, has a significant impact on firm-level innovation. This finding suggests that SASEC policy makers would do well to consider ways in which they could improve trade facilitation performance as one way of promoting innovation.
Keywords: South Asia -- Economic integration; Electronic books